Casein degradation of Fynbo cheese salted with NaCl/KCl brine and ripened at various temperatures - Sihufe, Guillermo Adrian (2003)
Effect of temperature and salt substitution on casein degradation of Fynbo cheese was studied. Fynbo cheeses, salted in solutions of 190 g NaCl/L and of 100 g NaCl/L and 100 g KCl/L and ripened at 5, 12, and 16 °C, were sampled at 1, 5, 10, 20, 30, 60, and 90 d of ripening, at central and external zones. Samples were analyzed for moisture and chloride contents, maturation index, and casein degradation by urea-polyacrylamide gel electrophoresis. NaCl replacement by KCl did not affect any of the parameters studied. Total salt concentration and ripening temperature affected proteolysis significantly. First-order kinetics constants for αs1-casein degradation were in the range of 0.002 to 0.016 day-1 and the activation energy of the reaction was approximately 26 kcal/gmol.